ОСОБЛИВОСТІ КЛАСИФІКАЦІЇ ЗЕРНА ПШЕНИЦІ ТА СИСТЕМА ЗАБЕЗПЕЧЕННЯ ЯКОСТІ БОРОШНЯНИХ ПРОДУКТІВ У КАНАДІОСОБЛИВОСТІ КЛАСИФІКАЦІЇ ЗЕРНА ПШЕНИЦІ ТА СИСТЕМА ЗАБЕЗПЕЧЕННЯ ЯКОСТІ БОРОШНЯНИХ ПРОДУКТІВ У КАНАДІ (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2026)
article explores the importance of unifying Ukraine’s national system for wheat grain classification and typology with internationally recognized classification systems to enhance the technological potential and competitiveness of Ukrainian wheat. It highlights the differences between Ukraine and other global markets, such as Canada, in how grain quality and consumer preferences are assessed. While Ukraine classifies wheat solely based on quality indicators, Canada employs a system that combines botanical characteristics with quality criteria. The article provides a detailed comparison of the Canadian classification system, which is known for its consistent high-quality wheat and significant global export share. The classification in Canada includes several distinct wheat classes, each serving specific end-uses like bread, pasta, and confectionery production. Moreover, Canada’s regulatory framework, overseen by institutions such as the Canadian Grain Commission, ensures the quality of wheat through strict standards and certification processes. The article also discusses the types of wheat flour available in North America, including all-purpose, bread, and whole wheat flours, and contrasts them with Ukrainian practices. The Canadian approach to wheat flour typology is considered more comprehensive, addressing the content of the wheat grain’s anatomical parts and the fineness of the milling, while also considering flour enrichment practices aimed at improving nutritional quality.
Keywords: wheat classification; grain typification; technological potential; competitiveness; grain quality; Canadian system; Ukrainian system; flour; grain market; wheat export; quality control